IDENTIFIKASI KUALITAS TELUR ITIK LOKAL YANG DIPELIHARA SECARA INTENSIF DI DESA BAGIKPOLAK, LOMBOK BARAT - Tamzil, Mohammad Hasil; Indarsih, Budi; Haryani, Ni Ketut Dewi; Jaya, I Nyoman Sukartha; Septian, I Gede Nano; Dewi, Nurul Afriani (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2025)
One of the factors that affect egg quality is the rearing system. The purpose of this study was to determine the quality of fresh local duck eggs obtained from members of the Karya Mandiri Duck Farmers Group. Egg collection was carried out in turns for 5 days from 5 farmers who had ducks in the egg-laying phase. Each farmer was randomly taken 10% of the total egg production, so that 105 eggs were collected. The external and internal quality of the sample eggs were then measured at the Animal Product Processing Technology Laboratory, Faculty of Animal Husbandry, University of Mataram. The results of the study found that the internal quality of the fresh duck eggs observed was classified as very good, but the external quality of 50% was classified as low. The local duck eggs from Lombok, produced by the Karya Mandiri Duck Farmers Group, are mostly of high quality, with 50% classified as grade AA. It is recommended to improve the housing system to further enhance quality.